Tested by fire the fruit of suffering in the lives of John Bunyan, William Cowper and David Brainerd - Piper, John, 1946- (Leicester, UK IVP, 2001)
Includes bibliographical references and indexes.
Keywords: Bunyan, John, -- 1628-1688; Cowper, William, -- 1731-1800; Brainerd, David, -- 1718-1747; Puritan examples -- Christian living